Digitization of library resources: challenges and implications for policy and planning (2006)
This paper examines the concept of digitization, it’s purposes and the process of digitization of library resources. The cognitive flexibility, relational communication and non-verbal immediacy communication theories were used for illustration. It also discusses the challenges often encountered during digitization and the implications for planning and policy. Digitization implies conversion of documents and art works into digital images. Digital images here mean electronic copies of documents. Digitization is a process in which materials are converted from the hard copies to electronic copies. The major purposes of digitalization are: to enhance access and improve preservation of library materials. A number of challenges are encountered in the process of digitizing library materials. These challenges include human and technical problems, which have implications for planning and policy. It was concluded that digitization is an essential task in modern day libraries, because of the current challenges, and the need to go digital, that is, provide online services.